Gifted travellers: rhetorical invention in seventeenth-century English travel writing - Din-Kariuki, N (2018)
This thesis argues that seventeenth-century English travellers drew on the precepts of rhetorical invention to understand and describe their experiences on the road. It focusses on the writings of Thomas Coryate, Henry Blount, William Scott, John Cartwright, and Edward Terry, all of whom travelled to the ‘Old World’ (Africa, Europe, and Asia, as opposed to the ‘New World’ of the Americas) for diplomatic, mercantile, and religious purposes in the period before 1660. It reconstructs aspects of the humanist pedagogy that these writers encountered at school and university to show that they used this intellectual training in settings far removed from their classrooms. It reveals that travellers drew on the topical approaches of a number of other genres, including the essay, tragedy, and the sermon. It examines the ethical and cognitive aspects of travel, demonstrating that practices of note-keeping were central to travellers’ regimens of self-knowledge and self-discipline. Setting travel writing within the discourses of natural philosophy and natural history, it shows that travellers, like other observers, were expected to transform the particulars of their experiences into universals, or general knowledge; it explains that this process, which was figuratively understood as ‘digestion’, inflected both the language and form of travellers’ works. It positions classical rhetoric as a background in which to see cross-cultural encounters in sharper relief, showing that travellers used their reading, and the precepts of invention, to bring things that were distant and unfamiliar closer to home. The first chapter situates Thomas Coryate’s eponymous Coryats Crudities (1611) within the contexts of ancient pilgrimage practices and classical understandings of ekphrasis, to show that Coryate fashions the account as a ‘tour’ that enables English readers to participate, as proxy witnesses, in his travels. Turning from Coryate’s ‘crudity’, the second chapter examines Henry Blount’s A Voyage into the Levant (1636), illustrating that Blount’s account is partly composed through the digestion of writings of Francis Bacon and Michel de Montaigne, and that its observations, though presented as the direct product of the traveller’s eyewitness experience, draw on earlier works by Bacon and George Sandys. The third chapter moves to discuss the anonymous Sir Thomas Smithes voiage and entertainment in Rushia (1605), and explains its emphasis on plotting, and the virtue of prudence, by reading it alongside classical and early modern theories of rhetorical disposition, including William Scott’s Model of Poesy; Scott may have been involved in the composition of Smithes voiage. The fourth chapter focusses on John Cartwright’s The Preachers Travels (1611), and explores the various strategies that Cartwright, a traveller whose reputation had been damaged during a previous expedition, employs to establish ethos and acquire credit. The final chapter studies Edward Terry’s A Voyage to East-India (1655), and it demonstrates that Terry draws on his training as a preacher, particularly the imperative to ‘apply’ passages of scripture to the auditory’s experience, in crafting his account. The thesis resituates travel writing as a creative, experimental, and theoretically sophisticated body of material, and broadens the scope of what early modern ‘literature’ might be said to comprise. More significantly, it offers a fresh assessment of the significance of travel to the cultural, intellectual, and literary life of early modern England, by showing that travel writing informed how this period thought about language, knowledge, cognition, governance, religion, and identity.